Sistem Informasi Persediaan Pada Zam Komputer Menggunakan PHP dan MYSQL - Saira Asmar; Indra kanedi; Venny Novita Sari (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
In this era, shops also really need a data management information system to simplify and expedite performance in storing large amounts of data, where the system that is still used is conventional where purchases still use notes, making it ineffective, with the existence of the "Inventory System in the Computer Age." Using PHP and MySQL” can help the Zam Computer shop. Zam Computer was established in Bengkulu on January 10 2018 at Jalan Bali, Kampung Bali, Teluk Segara District, Bengkulu City. Zam Computer operates in the IT (Technology Science) sector and sells computers and accessories. The research method that the author uses is the waterfall method, which is a sequential software development process where this method has several sequential stages: requirements (needs analysis), system design, coding and testing, program implementation and maintenance. The Goods Inventory Information System is a system used to input goods inventory data into a database, so that there are no errors in input, output and making reports based on the desired data. Having an inventory information system that can manage input and output as well as stock of goods can make work more effective and efficient. The process of purchasing products from suppliers to stores is also more efficient and helps business owners make more precise decisions.